Explaining criminal careers : implications for justice policy - MacLeod, John F.; Grove, Peter G.; Farrington, David P. (Oxford : Oxford University Press, 2012)
Using the Home Office Offenders Index, a unique database containing records of all criminal convictions in England and Wales since 1963, this simple but influential theory makes exact quantitative predictions about criminal careers and age-crime curves, in particular the prison population contingent on a given sentencing policy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Criminals -- Great Britain; Criminal justice, Administration of -- Great Britain